Contemporary pollen spectra in the James Bay Lowland, Canada, and comparison with other forest-tundra assemblages - Farley-Gill, L. (Géographie physique et Quaternaire, 1980)
Contemporary pollen spectra obtained from twenty-eight sites in the southwestern James Bay area were examined as an aid to the interpretation of postglacial pollen diagrams. Picea is the dominant pollen type. Pinus banksiana and Betula pollen are prominent, with the shrub birches contributing most of the latter. Other tree genera (Larix, Abies, Populus) extant in the area are underrepresented in the pollen assemblages. Among the shrub taxa present, pollen of two species of Alnus, A. crispa and A. rugosa, are regionally represented. Salix and Myrica pollen are notable locally at sites where these plants occur. Ericaceae values vary according to the type of sampling site. Cyperaceae and Sphagnum values fluctuate greatly depending on the proximity of these taxa to the sampling site. Pollen assemblages of the major taxa in six data sets extending from the forest-tundra of Saskatchewan to the eastern James Bay area in Québec were examined. Comparison yielded similar values of most genera. Local, regional and extra-regional influences, as well as over- and underrepresentation of individual taxa appear to apply uniformly over the entire area thereby providing pollen spectra representative of the forest-tundra of central Canada.